(untitled) (Medico Legal Update, 2020)
Injury to the anterior cruciate ligament (ACL) is one of the most common knee ligament injuries. The ACL injury is a sprain or tear of the anterior ligament (ACL). Effective exercises will reduce the risk of ACL injury. An ACL injury in athletes is a higher incidence than other general public, such as soccer, basketball, hockey, etc. The aim of this studywas to compare the effectiveness, recovery rate and variance in both knee-affected and non-affected muscle girth readings in supervised v/s unsupervised patient groups after the patient underwent ACL reconstruction surgery. The participants were divided into two groups(A-Supervised and B-Unsupervised) through a random sampling. The supervised exercise in group A performed according to the WILK protocol at RML hospital and un-superviseed group B performed the same WILK protocol at home. The ultrasound scans were performed after 2-4 weeks and 12-14 weeks post operation to measure the muscle girth in both the groups. The study findings indicated the significant difference in recovery rate as well as the difference in between supervisedv/s unsupervised groups i.e. the difference of affected and unaffected knees based on ultrasound imaging was higher in un-supervised group compared to supervised group (a difference of 2.3 mm in post-operation muscle girth after 12-14 weeks). The ultrasound reading of the muscle girth after 2-4 weeks post-operation showed a decline in the recovery of the muscle girth in both the groups (9% and 8% for supervised and un-supervised groups respectively). This reduction in the muscle girth value as compared to the pre-operative values was due to arthroscopic effect, which showed there was a transient deactivation of the muscle take place due to surgery. The ultrasound reading of the muscle girth after 12-14 weeks post-operation showed a different progressive recovery of the muscle girth in both the groups as 31% and 10% for supervised and un-supervised groups respectively .We concluded that supervised exercises was better than unsupervised exercises for the early recovery after ACL recontraction.